ACR Appropriateness Criteria® Locally Advanced, High-Risk Prostate Cancer. (February 2017) - McLaughlin, Patrick W.; Liss, Adam L.; Nguyen, Paul L.; Assimos, Dean G.; D'Amico, Anthony V.; Gottschalk, Alexander R.; Gustafson, Gary S.; Keole, Sameer R.; Liauw, Stanley L.; Lloyd, Shane; Movsas, Benjamin; Prestidge, Bradley R.; et al.
Abstract : Purpose: To present the most updated American College of Radiology consensus guidelines formed from an expert panel on treatment of locally advanced, high-risk prostate cancer Methods: The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer-reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment. Results: The panel summarized the most recent and relevant literature on the topic and voted on 4 clinical variants illustrating the appropriate management of locally advanced, high-risk cancer. Numerical rating and commentary reflecting the panel consensus was given for each treatment approach in each variant. Conclusions: Aggressive local approaches including surgery followed by adjuvant XRT, beam combined with androgen deprivation therapy, and beam combined with brachytherapy have resulted in unpresented success in locally advanced, high-risk prostate cancer. By combining most recent medical literature and expert opinion, this guideline can aid clinicians in the appropriate integration of available therapeutic modalities.